The effectiveness of problem-based learning in enhancing mathematical literacy: A systematic meta-analysis - Ahmad Gufron; Isti Hidayah; Ardhi Prabowo; Wardono; Scolastika Mariani (Jurnal Elemen, 2025)
This meta-analysis aims to evaluate the effectiveness of Problem-Based Learning (PBL) in improving students' mathematical literacy by reviewing empirical studies comparing PBL with conventional learning. The results show that PBL significantly improves mathematical literacy, with an effect size of 1.165, categorized as high. However, the effectiveness of PBL is influenced by moderating factors such as education level, student learning style, learning duration, and problem relevance. Findings suggest that PBL is more effective at the junior high school level than senior high school, although the difference is not statistically significant (p > 0.05). This study is limited by the short intervention duration in most analyzed studies and the lack of investigation into external factors like student motivation and teacher roles. Future research is recommended to conduct longitudinal studies, explore the integration of digital tools, and compare the use of real-world and academic problems in PBL. Overall, the findings confirm that PBL is an effective and promising approach for enhancing mathematical literacy when implemented with attention to relevant contextual and learner-specific factors.